Learning Difficulties: Diagnosis, Prevention, Overcoming - E.I. Isaev; A.A. Margolis (Moscow State University of Psychology and Education, 2023)
Analysis of the theory and practices of overcoming learning difficulties has shown that the existing pedagogical and psychological approaches are not effective enough. They do not take into account the connection between learning and development processes. More productive is the approach of cultural-historical psychology, which considers education as a developmental process. This approach can be used to create an effective system of diagnostics, prevention and correction of learning difficulties. The model of such pedagogical activity includes three levels of individualization of learning: from individual planning of lessons to individual lessons for correction of psychological problems, and it was presented in this study.